2018
DOI: 10.21037/jtd.2018.01.115
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular assist device exchange for the treatment of HeartMate II pump thrombosis

Abstract: Between February 2004 and December 2015, 87 exchanges of LVADs were performed at a single center. In 41 cases pump thrombosis was the reason for LVAD exchange. A total of 28 patient years (10,276 days) were analyzed. Average ICU stay was 15.8±20.4 days and average in-hospital stay 38.1±37.3 days after LVAD exchange. After thirty days the survival rate was 80.5%, 75.6% after 6 months and 70.7% one year after LVAD exchange. Out of the study cohort, three patients have successfully undergone heart transplantation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…As a result of the rise in heart failure, the use of ventricular assist devices that promote blood flow will increase. While advancements in VAD design have reduced shear stress, VADs are still a significant source of hyper-shear forces [15], leading to shear-induced thrombosis [51]. As such, it is essential to understand the mechanical activation of platelets and how it may differ from other modes of activation.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of the rise in heart failure, the use of ventricular assist devices that promote blood flow will increase. While advancements in VAD design have reduced shear stress, VADs are still a significant source of hyper-shear forces [15], leading to shear-induced thrombosis [51]. As such, it is essential to understand the mechanical activation of platelets and how it may differ from other modes of activation.…”
Section: Discussionmentioning
confidence: 99%
“…Previously published single-center data estimate the overall risk of recurrent device thrombosis after device exchange for the same to be between 21% and 33%. 6,17 Hanke et al 7 analyzed a cohort of 16 patients supported with HeartMate II who underwent device exchange for pump thrombosis. Within the first year, two patients were transplanted, one was explanted for recovery, and four died.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that LVAD exchange is technically possible, 6,7 but not without perioperative risks 8 . The less invasive subcostal approach for HMII exchange has been shown to have numerous benefits compared with re‐entry median sternotomy, including decreased transfusion requirements, shorter hospital length of stay, and improved overall survival 1,2,9 .…”
Section: Commentmentioning
confidence: 99%
“…Numerous studies have demonstrated that LVAD exchange is technically possible, 6,7 but not without perioperative risks. 8 The less invasive subcostal approach for HMII exchange has been shown to have numerous benefits compared with re-entry median sternotomy, including decreased transfusion requirements, shorter hospital length of stay, and improved overall survival. 1,2,9 A less invasive approach for HM3 exchange is considered more technically challenging given the newer device's intrapericardial location and lack of associated pump pocket, reducing the physical space the surgeon is afforded to operate.…”
Section: Commentmentioning
confidence: 99%